2014
DOI: 10.1007/s12011-014-9913-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Toxic and Nutritional Essential Elements in Meat from Different Beef Breeds Reared under Intensive Production Systems

Abstract: Concentrations of major nutritional and trace elements (Ca, P, Mg, Na, K, Fe, Zn, Cu, Mn, Se, Co, Cr, Ni, Sr, and Ba), as well as toxic heavy metals (Cd and Pb), were analyzed in the longissimus muscle of Charolais, Hereford, and Simmental bulls. The elements were determined using inductively coupled plasma optical emission spectrometry. The study showed that the breeds differed in the concentrations of K, Mg, Zn, Cu, Fe, and Mn in meat. Meat from Charolais bulls had a significantly higher K (P < 0.01) content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 36 publications
9
22
2
1
Order By: Relevance
“…Similarly to what we found for beef quality traits, the mineral profile was hardly affected by the animal's breed and sex, as the only significant differences were among breeds for the content of Ca and B, and between young bulls and heifers for the content of K, Zn, Sn, and Pb [23]. Very few of the many studies carried out on the mineral content of beef have compared different cattle breeds [31][32][33][34] or sexes [35][36][37], and most have confirmed the modest effects of these sources of variation. From these results, it seems unnecessary to study the relationships between the mineral profile and beef quality within specific breeds or sexes.…”
Section: Mineral Profile Of Beef and Its Relationship With Animal Persupporting
confidence: 61%
“…Similarly to what we found for beef quality traits, the mineral profile was hardly affected by the animal's breed and sex, as the only significant differences were among breeds for the content of Ca and B, and between young bulls and heifers for the content of K, Zn, Sn, and Pb [23]. Very few of the many studies carried out on the mineral content of beef have compared different cattle breeds [31][32][33][34] or sexes [35][36][37], and most have confirmed the modest effects of these sources of variation. From these results, it seems unnecessary to study the relationships between the mineral profile and beef quality within specific breeds or sexes.…”
Section: Mineral Profile Of Beef and Its Relationship With Animal Persupporting
confidence: 61%
“…Comparing the mass fraction of nutrients obtained in several types of meat with the results reported in the literature, it could be observed the similarity with the obtained results in the current work. 2,4,12,17,19 0.71 ± 0.01 0.88 ± 0.03 0.37 ± 0.06 0.53 ± 0.02 Zn / (mg kg -1 ) 29.85 ± 0.01 77 ± 1 57 ± 4 121 ± 3 LOD: limit of detection (Cu: 3 mg kg -1 ).…”
Section: Meat Samples Analysismentioning
confidence: 99%
“…1 The mineral content in meat varies, depending on factors such as diet, environmental conditions, cut and breed of the animal. [2][3][4] Meat is a food rich in minerals such as Ca, Mg, Fe, P, and S, which are found at high levels, whereas other essential minerals, such as Cu, Mo, Se, Zn, and Co are present in trace amounts. 5 In the literature, numerous studies have reported different analytical methods for the quantification of these elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minerals are essential and/or toxic, and this depends on their functions and on their level of concentration in food matrices (Schmitt et al , ). Minerals composition in beef could be categorised such as macrominerals and essential and environmental microminerals (García‐Vaquero et al , ; Pilarczyk, ). Meat mineral concentrations are affected by several sources of variations which include intrinsic factors, such as muscle type, animal breed, sex and age, and extrinsic factors, such as diet, water, farm management and environmental conditions (Giuffrida‐Mendoza et al , ; Ramos et al , ; Schönfeldt & Hall, ; Domaradzki et al , ).…”
Section: Introductionmentioning
confidence: 99%